Historical and scientific analysis of Iranian illuminated manuscripts and miniature paintings - Barkeshli, Mandana (The Iranian Academy of Art, 2009)
The present study aims to identify the materials and techniques used in Persian illuminated manuscripts and miniature paintings and its major significance in comparison with Indo-Iranian and Mughal paintings. The research methodology was based on oral interviews with traditional masters, historical analysis and scientific analysis.